Multivariate Bayesian analysis for genetic evaluation and selection of Eucalyptus in multiple environment trials - Ferreira, Filipe Manoel; Evangelista, Jeniffer Santana Pinto Coelho; Chaves, Saulo Fabricio da Silva; Alves, Rodrigo Silva; Silva, Dandara Bonfim [UNESP]; Malikouski, Renan Garcia; Resende, Marcos Deon Vilela; Bhering, Leonardo Lopes; Santos, Gleison Augusto (FapUNIFESP (SciELO), 2022)
Forest plantations are strong allies in preserving natural resources, providing social and economic benefits. The plantations carried out in the coming years will be vital to meet the growing demand for forest products. To ensure the continuity of genetic progress and the good results achieved with the improvement of forest species, statistical methods that accurately selects superior genotypes are desirable. Multi-trait multi-environment trials are preferred over single-trait single-environment trials, since they can exploit the covariance between traits and environments, increasing the analysis’s prediction power. The Bayesian multi-trait multi-environments approach (BMTME) combines the cited advantages with the parsimony of Bayesian statistics promoting a more informative data analysis. Thus, the aims of this study were to estimate genetic parameters, evaluate genetic variability, and select eucalyptus clones through BMTME models. To this end, a data set with 215 eucalyptus clones evaluated in four environments for diameter at breast height and Pilodyn penetration was used. The Markov Chain Monte Carlo algorithm was applied to estimate the variance components and genetic parameters and to predict the genotypic values. The Smith-Hazel index was used to simultaneously achieve gains with selection for both traits. The BMTME approach provided high accuracies, being a good strategy to the evaluation of multiple environmental trials of Eucalyptus for breeding purposes.
Keywords: Eucalyptus spp; forest tree breeding; genotype × environment interaction; multi-environment trials; quantitative genetics